Development and Evaluation of the Virtual City - Brown, David; Neale, Helen; Cobb, Sue; Reynolds, Hugh (International Journal of Virtual Reality, 1999)
house, a supermarket, a café and a transport system. Evaluation of the project was concerned as much with the design of the virtual learning environments (VLEs), issues of usability and access as with monitoring skill learning and transfer to the real world. For three of the VLEs, Supermarket, Café and Transport, a test-retest experimental design method was used. This compared user performance in real world tasks with the same tasks presented in the VLE. Expert assessment was used to evaluate the Virtual House, looking at usability and appropriateness of the learning scenarios. It was found that VLEs can provide interesting, motivating learning environments, which are accessible to users with special needs. Individuals differed in the amount of support required to use the input devices and achieve task objectives in the VLE. Expert and user review methods indicated that the VLEs are seen to be representative of real world tasks and that users are able to learn some basic skills. However, it would be unrealistic to expect transfer of skill over a short experimental time. Further testing is needed to establish the longitudinal learning effects and to develop more reliable techniques to allow users to express their own opinions. Within this project the value of a user centred approach has been demonstrated. The groups involved have provided informed input at each stage of VE development. This has been enhanced by contributions from experts in the field of learning disabilities. The Virtual City has been developed in response to the needs of people with learning disabilities, not in response to their assumed needs.